2017
DOI: 10.1186/s13049-017-0442-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing on-scene time in a rural Norwegian helicopter emergency medical service: a retrospective observational study

Abstract: BackgroundCritically ill patients need to be immediately identified, properly managed, and rapidly transported to definitive care. Extensive prehospital times may increase mortality in selected patient groups. The on-scene time is a part of the prehospital interval that can be decreased, as transport times are determined mostly by the distance to the hospital. Identifying factors that affect on-scene time can improve training, protocols, and decision making. Our objectives were to assess on-scene time in the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
(43 reference statements)
4
15
0
Order By: Relevance
“…The analysed group of patients consisted mainly of males who made up two-thirds of the entire group, and persons aged 50-64, mean age of the whole group -47.71 years. The results of the authors' own research concerning demographic data of the patients are similar to results obtained by other authors, such as Østerås et al and Kottmann et al [22,23].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The analysed group of patients consisted mainly of males who made up two-thirds of the entire group, and persons aged 50-64, mean age of the whole group -47.71 years. The results of the authors' own research concerning demographic data of the patients are similar to results obtained by other authors, such as Østerås et al and Kottmann et al [22,23].…”
Section: Discussionsupporting
confidence: 89%
“…In Sweden, a study carried out by Kornhall et al concerning HEMS missions in rural areas, showed that the main reasons for the missions were injuries, chest pain and sudden cardiac arrest [23]. In Norway, similar results were obtained by Østerås et al in their study concerning HEMS missions [22].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…On-scene-time depends on several factors including type of accident (trauma or cardiac), severity of injury, therapeutic measures (such as fixation, intubation, etc. ), and the patient transportation type [19].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the fact that the main reason for transport by HEMS in the current study was trauma, the most taken measures were related to the fixation of various body organs. In some studies conducted in Iran [14,19].…”
Section: Discussionmentioning
confidence: 99%